Family Interactions and Emotional Development of a Five-Year-Old Children - Rodríguez, Andrea Ivett; Sanabria, Nelsy Teresa (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article presents the family interactions and emotional development of a five-year-old boy from Gámeza, Boyacá, from the description of daily interactions, the interpretation of parental styles, and the visibility of factors that affect the child’s emotional development. The study used the qualitative method with an interpretative approach from the point of view of the case study. The interactions with the family came to techniques and tools such as participant observation and semi-structured interviews. The above, considering the categories emotional intelligence and parenting styles. The contributions of research and studies on the subject validate the importance of family relationships and their emotions. Also, the results showed the incidence of parental styles on the emotional development of children, which became evident in the relationship between the child and the culture and daily experiences between parents and children, which are the basis for a personality formation. The personality is built on participatory and democratic relations.